Directional Asymmetry in Random Waves Near Shallow Water Regions – Its Application in Physical Modelling. (2015) - Jagadeesh, H.B.; Rao, Subba; Nagendra, T.; Chalawadi, A.S.
Abstract: In coastal engineering, short wave basin physical model studies have played a very vital role to support the optimization of harbour layout planning. Basically, these models are economical tools for simulation of complex 3-D wave process as in nature with 2-D approximation near wave generation boundary in model. The 2-D state of short period waves generated in model will transform to attain 3-D state due to directional spreading while travelling from the point of generation to the various locations of observations in the model. This transformation process in model depends on various factors like wave approach, bathymetric conditions, interaction with port structures etc. The wave refraction due to oblicity of the wave crest with the sea bed contour in the model is a dominating phenomenon which causes the directional spreading in the model. A shallow basin rigid bed physical model, equipped with random sea wave generating facilities from three directions, has been used to study the directional spreading of waves in the model from the wave generating point to different points of interest within the model. Based on these studies the directional changes for different oblicity of wave approach with respect to sea bed bathymetry in the model was identified. This serves as a good guideline for the location of wave generation boundary in the shallow basin physical model. This is useful in initial planning of the physical model like in identifying the size of the model try and model scale selection.